Opportunities of Natural Plant Materials as Alternative Antibacterials in Drinking Water Disinfection: Review Article - Ahmad, Rahwan; Prasetyawati, Prasetyawati; Assagaf, Farha; Kaluku, Khartini (Poltekkes Kemenkes Maluku, 2025)
Various efforts to kill pathogenic bacteria in water with safer and more economical disinfectants continue to be pursued. The presence of antibacterial agents in plants can be a promising alternative to natural disinfection. This review discusses the use of natural materials as safer and more economical alternative disinfectants in the water disinfection process. Methods, This is a narrative review using sources from the ProQuest database. The key terms “Extracts AND Plants AND